I Got Algorithm: Can There Be a Nate Silver in Intelligence? - Spielmann, Karl (International journal of intelligence and counterintelligence, 2016)
Nate Silver is a prominent statistician / statistical probability analyst who, among other achievements, maybe best known for making a very accurate prediction of Pres Barack Obama's victory and its dimensions in the 2012 election. In doing so, he probably redeemed the reputation of sophisticated mathematical modeling that was badly tarnished by its association with the poor investment decisions that brought the financial debacle of 2008. Nevertheless, in presenting the methodology on assessing and predicting threats, the author has explicitly noted that analysts might well look to statistical probability analysis as another way to gain confidence that their particular hypothesis on some threat is on target.